Taxonomic notes on the genus Anthaxia Eschscholtz, 1829 (Coleoptera: Buprestidae: Anthaxiini) 1. - Baiocchi, Daniele (Zootaxa, 2015)
In the present paper I propose the following taxonomic changes: Anthaxia (Haplanthaxia) bosdaghensis Obenberger, 1938 (= cavazzutii Bílý, 1980 syn. nov.); A. (Anthaxia) ephippiata Redtenbacher, 1850 (= kreuzbergi Richter, 1944 syn. nov.); A. (H.) pleuralis Faimaire, 1883 (= parapleuralis Obenberger, 1929 syn. nov.); A. (H.) scylla Levey, 1985, removal from synonymy (= aprutiana Gerini, 1955 unavailable name); A. (A.) truncata Abeille, 1900 (= lgockii Obenberger, 1917 syn. nov.; = talyshensis Bílý, 1991 syn. nov.; = adiyamana Svoboda, 1994 syn. nov.). Lectotypes for A. (A.) kreuzbergi, A. (H.) parapleuralis and A. (A.) truncata are designated. All the studied types are illustrated, together with their original data labels. Each of the valid species is placed in its respective species-group, and notes are given on the distribution.